Welas Asih: Konsep Compassion dalam Kehidupan Masyarakat Jawa - Dwi Hardani Oktawirawan; Taufik Akbar Rizqi Yunanto (Universitas Negeri Medan, 2021)
Welas asih is a Javanese behavior where one feels the pain of others which then arouse the desire to help. In its application, one can provide help to others even for those who are not relatives. This is inseparable from the various philosophies that exist in Javanese society that make welas asih as a way of life. This paper is made to review the concept of welas asih of the Javanese community which is then juxtaposed with the concept of psychology. The concept of psychology in question is compassion which also refers to the ability of someone to feel the suffering of others and the urge to alleviate or eliminate the suffering. So that an explanation of welas asih of the Javanese people will be revealed in a psychological perspective.